Poéticas de um saber brincar: a vez e a voz do fandango - Canella, Ricardo Elias Ieker (2009)
The present thesis aims to get to know and to analyze the elements which make up the poetical performance of the Fandango from Canguaretama confirming/corroborating an eminently theatrical model. It still highlights the producers´ history, its asset production and its insertion in community where we had contact with two other types of performances: the daily and the ritualistic. Such actions both combine and present different meanings and objectives, promoting distinct readings and experiences. Looking at these three ways of performances poetic, daily, and ritual enabled to go deeper in cultural aspects of the studied community and, thus, check over what is going on in these events, how they accord with and conceive a popular performance context. The research could substantiate the existence of a theatrical model whose performance by means of the voice and active presence of playful bodies, implied in getting to know the consolidation of a cultural patrimony which reveals us the past, but, especially, the present, its people and its place